TWO C-GLYCOSIDE FLAVONES FROM CORN (ZEA MAYS) SILK - Ren, Shuncheng (African Journal of Traditional, Complementary and Alternative Medicines, 2018)
Background: Corn silk, a traditional Chinese herbal medicine in China, has been used to remedy nephritis, hepatitis,measles, hyperglycemia, tumor, etc. In this study, flavonoid monomers in corn silk were isolated and identified. Thisstudy could serve as a basis for determining the curative effects of these monomers on human diseases.Method: Corn silk flavonoids were extracted using 80% (v/v) ethanol and isolated by repeated polyamide column andToyopearl HW-40 column chromatography. Corn silk flavonoids were identified by UV spectroscopy, liquidchromatography/mass spectroscopy, and nuclear magnetic resonance spectroscopy.Results: Two C-glycoside flavones, namely, ax-4″-OH-3′-methoxymaysin and a 3′-methoxymaysin isomer, wereisolated from corn silk and identified.Conclusion: The two C-glycoside flavones were successfully isolated from corn silk and identified. This study is thefirst to report 3′-methoxymaysin in corn silk.